Analysis of the relation between health statistics and eating habits in Japanese prefectures using fuzzy robust regression model. (1st May 2016) - Yabuuchi, Yoshiyuki; Kawaura, Takayuki; Watada, Junzo
Abstract: In recent years, the Japanese Ministry of Health, Labour, and Welfare is working to improve citizen׳s lifestyle and social environment to improve their health. This is because of the following reasons. Diseases related to lifestyle such as malignant neoplasms, heart disease, and cerebrovascular disease account for about 60% of the deaths in 2013. In addition, 32% of all medical expenditures are made on lifestyle-related disease. Lifestyle-related diseases can be prevented by daily exercise, a well-balanced diet, and not smoking. This ministry is promoting measures such as dietary education, physical activity, and exercise. Improvement of diet is the easiest way to reduce the occurrence of lifestyle-related diseases. Thus, in this paper, we analyze the relation between health and diet using our fuzzy robust regression model.